2005
DOI: 10.1017/s0021932005026489
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Educational Attainment and Intergenerational Patterns of Fertility Behaviour in Kenya

Abstract: There is a strong theoretical and empirical relationship between educational attainment and fertility behaviour. However, a fundamental issue that has largely been neglected is the change in this relationship across cohorts resulting from differential improvement in educational opportunities for women over time and how it relates to fertility transition. Utilizing the 1998 DHS data from Kenya this study examines the differential effect of educational attainment on women's use of modern contraception and desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…In the past, rural women reported longer birth intervals due to lengthened breastfeeding (Millman 1986). In contrast, urban versus rural women use modern contraception in higher proportions-methods which are more reliable in birth spacing and reducing the overall number of children born (Omariba 2006).…”
Section: Disruption and Adaptationmentioning
confidence: 99%
“…In the past, rural women reported longer birth intervals due to lengthened breastfeeding (Millman 1986). In contrast, urban versus rural women use modern contraception in higher proportions-methods which are more reliable in birth spacing and reducing the overall number of children born (Omariba 2006).…”
Section: Disruption and Adaptationmentioning
confidence: 99%
“…Higher education levels among women have consistently been associated with lower fertility and greater contraceptive use, although the exact mechanisms through which education is related to such outcomes have not been identified. 8,[14][15][16][17][18][19][20] Previous studies have found that sterilization-male or female-was the most commonly used method among couples in which the woman had a low education level, particularly in South Asia, where government family planning programs tend to focus on poor, uneducated rural women. 8,[21][22][23][24] These studies showed that women with higher levels of education were more likely to rely on reversible methods than on permanent methods.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study carried out in Nepal indicates that education exposes women to information, empowers women and makes them more likely to be employed outside their home environment and makes them more aware of their own health and health of their children. Educated women are more likely to postpone marriage, have small family size and use contraceptives more than the uneducated women [1,10,31]. We therefore recommended that government and non-governmental agencies should embark on public enlightenment campaign to create awareness on the importance of fertility control.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the linkage between fertility and poverty has not been fully explored. Most studies in Kenya have looked at the socioeconomic determinants of fertility by examining the differentials in education [31] and urban rural fertility differentials [37]. Therefore this study will strive to understand the fertility differentials among the poor womens in Kenya and the factors leading to fertility differentials using the Bongaarts analytical model of 1978.…”
Section: Introductionmentioning
confidence: 99%